Took : a ghost story - Hahn, Mary Downing (Clarion Books, 2015)
At first Daniel and Erica do not believe the superstitious tales of their mean new classmates. They tell them that their new home, a rundown farm, is haunted by Old Auntie, a witch who kidnaps and keeps a girl for fifty years, then lets her go to get another one. When Erica is taken, Daniel knows he cannot ignore the truth of Old Auntie anymore, and summons his courage to take his sister back.